2008
DOI: 10.1111/j.1751-9020.2007.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

The State of Media Ownership and Media Markets: Competition or Concentration and Why Should We Care?

Abstract: This article presents a global overview of the state of communications media ownership and markets. The primary issue at stake is whether or not markets and ownership are becoming more or less concentrated. After reviewing contrasting views on this issue, I suggest that the question turns on whether or not we consider 'numerical diversity' (the number of channels available in any given area) versus 'source diversity' (a measure of the number of media owners in any given area). Drawing on recent data I suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 3 publications
0
34
0
4
Order By: Relevance
“…For this research we reviewed the annual reports of the CMT ( (2002), Noam (2009), Picard (1996 and Winseck (2008).…”
Section: Methods and Approachmentioning
confidence: 99%
“…For this research we reviewed the annual reports of the CMT ( (2002), Noam (2009), Picard (1996 and Winseck (2008).…”
Section: Methods and Approachmentioning
confidence: 99%
“…Equally, major Internet start-up companies have emulated media conglomeration through mergers and acquisitions to extend their own market dominance. Winseck (2008), for example, suggests that Google's dominance of the search engine market introduces 'a phenomenon that we might call a "Googlopoly"' (43).…”
Section: Organisational Convergencementioning
confidence: 99%
“…The advances in the information technology, in particular the Internet, have helped contribute to the variety of channels, yet not led to the diversity of views in the news (Winseck, 2008). Murdock also observed that, although there's an increase in the number of the news channels, there is no increase in diversity and he said, 'plenty of news doesn't always mean a diversity of news, ' (1982: 120).…”
Section: Theoretical Frameworkmentioning
confidence: 99%